THE ROLE OF FARMERS' GROUPS IN RICE FARMING IN WEHALI VILLAGE, MALAKA TENGAH DISTRICT, MALAKA REGENCY - Agustina Nahak; Ernantje Hendrik; Selfius P.N. Nainiti (Undana Press, 2026)
Lowland rice farming in Wehali Village, Central Malaka District, Malaka Regency, still faces various problems, including low productivity, limited farmers’ knowledge and skills, weak access to capital and technology, and the suboptimal role of farmer groups in supporting farming activities. In fact, farmer groups have a strategic role as learning classes, cooperation forums, and production and marketing units in improving the performance of lowland rice farming. This study aims (1) to identify the characteristics of lowland rice farming, (2) to analyze the role of farmer groups in lowland rice farming, and (3) to determine the factors related to the role of farmer groups in Wehali Village. The study was conducted in May 2025 using a survey method. The research location and respondents were determined through purposive sampling involving three active farmer groups with a total of 60 farmer respondents. Data were collected through interviews, observations, and questionnaires, and analyzed descriptively. The results show that (1) the characteristics of lowland rice farming in Wehali Village are dominated by farmers with relatively small landholdings and low levels of education; (2) the role of farmer groups is generally categorized as moderately effective, particularly as learning classes and cooperation forums, while their role as production and marketing units has not been optimally implemented; and (3) factors related to the role of farmer groups include education level, farming experience, and farmer participation in group activities. The conclusion of this study indicates that strengthening the role of farmer groups through improved extension services, training programs, and cooperation with relevant stakeholders is necessary to enhance the productivity and sustainability of lowland rice farming in Wehali Village.